Adverse childhood experiences are associated with at-risk drinking, cannabis and illicit drug use in females but not males: an Emergency Department study. (1st November 2020) - Cunradi, Carol B.; Caetano, Raul; Alter, Harrison J.; Ponicki, William R.
ABSTRACT: Background: Adverse childhood experiences (ACEs) are associated with adult substance use in the general population. Given pervasive health disparities among underserved populations, understanding how ACEs are associated with substance use among urban Emergency Department (ED) patients could help inform design of effective screening, brief interventions, and referral to treatment. Objectives: To estimate gender differences in prevalence of separate and cumulative ACEs among a sample of urban ED patients, and assess its association with at-risk drinking (4+/5+ drinks for females/males), cannabis, and illicit drug use. We hypothesized that the association between ACEs and each outcome would be stronger among females than males. Methods: Cross-sectional survey data were obtained from 1, 037 married/partnered ED patients (53% female) at a public safety-net hospital. Gender-stratified logistic regression models were estimated for each substance use outcome. Results: One+ ACEs were reported by 53% of males and 60% of females. Females whose mother was a victim of domestic violence had greater odds of at-risk drinking compared to females who did not report this ACE (AOR = 1.72; 95% CI 1.03, 2.88). Females' cumulative ACEs were associated with cannabis use (OR = 2.26, 95% CI 1.06, 4.83) and illicit drug use (OR = 3.35; 95% CI 1.21, 9.30). Males' separate and cumulative ACEs were not associated with increased likelihood for any of the outcomes. Conclusion: ACEs are associated with greater odds of substance use among female than male ED patients. The prevalence of ACE exposure in this urban ED sample underscores the importance of ED staff providing trauma-informed care.